PERAN WANITA DALAM MENUNJANG PEREKONOMIAN RUMAH TANGGA KELUARGA PETANI TRADISIONAL UNTUK PENANGGULANGAN KEMISKINAN DI DESA KUWIL KECAMATAN KALAWAT - Aswiyati, Indah (HOLISTIK, Journal Of Social and Culture, 2016)
In general, working women are not only to spend their spare time or develop their career. The aim of this research is to investigate the role of women in supporting the tradisional farmer household economic at Kuwil village Kalawat sub-regency. Descriptive method used by the researcher in giving explanations about the facts toward the aim. The result showed that women role as wives or house wives of tradisional farmer in increasing the farmer household economy in Kuwil village Kalawat sub-regency. The role was relatively important and strong because the process of taking decision related to economic and social needs for the family dominated by them. Keywords: Women role in family